Compact Ku-Band Orthomode Transducer Using Plus-Shaped Waveguide - Jongmin Lee; Sungmin Noh; Sangpil Lee; Jinho Jeong (IEEE Access)
This paper presents a compact Ku-band orthomode transducer (OMT) utilizing a plus-shaped waveguide (P-WG), which allows for the effective separation of vertical and horizontal polarization fields in a compact form factor. The proposed P-WG, with a characteristic impedance intermediate between that of the input square waveguide (S-WG) and the output rectangular waveguide (R-WG), enables the use of an iris for impedance matching instead of a bulky multi-step impedance transformer, thereby facilitating miniaturization. Additionally, small-square waveguides (SS-WGs) are employed to effectively suppress in-band spurious resonances, further broadening the bandwidth. Measurements of the fabricated OMT demonstrate notable characteristics: return loss exceeding 10 dB for vertical polarization from 13.5 to 17.5 GHz and for horizontal polarization from 13.6 to 16.7 GHz, insertion loss below 0.8 dB, isolation over 46 dB, and cross-polarization levels above 41 dB, confirming its suitability for Ku-band applications.